ANALYSIS OF THE IMPLEMENTATION OF DENTAL AND ORAL HEALTH SERVICE STANDARDS FOR BPJS PARTICIPANTS AT THE BINJAI VILLAGE HEALTH CENTER IN 2022 - Sabar Menanti; Balqis Wasliati; Rahmad Gurusinga (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
On January 1, 2014, the Indonesian government has implemented the BPJS health insurance program to ensure and support healthcare services. In the Binjai Village Health Center, the healthcare facilities (equipment and consumables) are not complete. For example, the dental unit is damaged or not functioning properly, the competence of dentists and dental nurses is not well coordinated, and there is a lack of communication patterns between healthcare personnel and patients. This research was conducted using a qualitative approach with eight informants. Data collection was done through observation and in-depth interviews. The results of the study indicate that the healthcare facilities in the dental and oral health department are not complete; dentists and dental nurses have professional licenses (SIK and SIP), but they need to be extended; the Binjai Village Health Center does not have specific standard operating procedures for the dental and oral health department; and the dental and oral health services for BPJS patients have not met expectations due to actions that have not been taken. It is highly expected that the Binjai Village Health Center promptly improves its healthcare facilities and conducts a registration of personnel with professional licenses (SIK and SIP). Program planning for the department should consider dental and oral health personnel participating in activities or training to update their knowledge in accordance with current developments.